Life Across the River: Exploring the Impact of Urbanisation in 18th–19th Century Panevėžys - Brindzaitė, Rūta (Archaeologia Lituana, 2020)
Studies aimed at considering the impact of industrialisation, urbanisation and modernisation on human health in 19th-century society are becoming increasingly relevant. Although it is exceptionally rare to encounter human skeletal material from the 19th century in present-day Lithuania, this study explores whether changes which occurred in that century had any impact on human health. This research presents the preliminary results of an anthropological analysis of the human remains discovered in Panevėžys Cemetery, with material spanning the 18th–19th centuries. In total, 90 individuals were examined, including 57 males, 15 females and 18 nonadult individuals. Fractures and nonspecific inflammatory lesions were the most prevalent pathological changes. However, the values of the average height of males and females did not reveal a significant change in stature. Overall, the results demonstrated inconsistent evidence of the effects of urbanisation on the skeletal population. It can be concluded that both the sample size and the observed pathologies represent only part of the community. Therefore, a more representative sample and additional analyses are required in the future, to provide comprehensive results and more solid conclusions.
Keywords: 19th century; human remains; bioarchaeology; palaeopathology; Lithuania; Panevėžys